2020
DOI: 10.1111/cea.13784
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of eczema in children and adults in England: A population‐based study using primary care data

Abstract: Background Whilst eczema is a common inflammatory skin condition, we lack contemporary estimates of disease incidence and prevalence across the lifespan. Objective To estimate the incidence and prevalence of eczema in children and adults in England and variation by sociodemographic factors (sex, socio‐economic status, ethnicity, and geography). Methods We used the Royal College of General Practitioners Research and Surveillance Centre primary care research database of 3.85 million children and adults registere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 51 publications
4
38
0
Order By: Relevance
“…Although there are a few other studies that focus specifically on the epidemiology of atopic dermatitis among older adults, review of additional population-based cohorts, including the US NHANES validation cohort presented herein, the 2010 US National Health Interview Survey (NHIS) data [ 23 ], and two additional UK-based sources [ 24 , 25 ] support our findings. The period prevalence of self-reported atopic dermatitis in the 2010 NHIS was similar to our findings: 9.0% among younger adults ages 18–32 and 11.4% among older adults ages 62–85.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Although there are a few other studies that focus specifically on the epidemiology of atopic dermatitis among older adults, review of additional population-based cohorts, including the US NHANES validation cohort presented herein, the 2010 US National Health Interview Survey (NHIS) data [ 23 ], and two additional UK-based sources [ 24 , 25 ] support our findings. The period prevalence of self-reported atopic dermatitis in the 2010 NHIS was similar to our findings: 9.0% among younger adults ages 18–32 and 11.4% among older adults ages 62–85.…”
Section: Discussionsupporting
confidence: 66%
“…A systematic review and meta-analysis found that atopic dermatitis is more common among groups with higher SES, though these were primarily studies of children [ 33 ]. More recent studies have found that this association was strongest early in life, but that atopic dermatitis was more common among lower socioeconomic groups in adulthood or did not vary by SES [ 5 , 25 , 34 ]. Additional study is warranted to explore possible mechanisms for these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal evidence suggests benefit of maternal dietary restriction for some children with chronic symptoms associated with food allergy, such as eczema 4 . Eczema is the most burdensome skin condition worldwide, with a high prevalence during the first 2 years of life 8 and limited non‐pharmacological options for management. Some families may feel that maternal dietary restriction is safer than using medical products such as skin creams, wash products and topical anti‐inflammatories.…”
Section: Can Healthcare Practitioners Safely Advise Maternal Dietary ...mentioning
confidence: 99%
“…The healthy skin microbiota changes considerably throughout life, with Staphylococcus and Streptococcus dominating in infancy, while Cutibacterium and Corynebacterium are more abundant in adulthood (Figure 2A). 67,70,124,125 Interestingly, the prevalence of AD is highest in the first years of life, with a considerable decline around school age 126,127 (Figure 2B), and while AD can resolve in some cases, for others it becomes a lifelong condition. 86 Interestingly, the skin microbiota in young children is also quite different from that of older children and adults.…”
Section: Disease Initiation and Early Ad Developmentmentioning
confidence: 99%